European Higher Education Area, internationalization and students’ mobility in 21st century - Kavasakalis, Aggelos; Gkiza, Theodora (Advances in Social Sciences Research Journal, 2022)
Higher Education Institutions (HEIs) seem to be influenced by the evolutions of globalization, to modernize and operate according to the knowledge society and therefore preparing and equipping students with the appropriate knowledge and skills required in order to respond to new situations imposed by the modern globalized environment. A principal axis is the internationalization of the teaching and learning provided in order to increase the competitiveness among institutions, improve the quality of the provided services and lastly integrate an international as well as intercultural dimension in the purpose, the functions and the mission of an institution (De Wit, 2015; Knight, 2004). The aim of the present article is to provide a theoretical reflection on internationalization and student mobility (which is an internationalization policy) in European Higher Education Area in the 21st century. The first section will attempt to delineate the concept of internationalization and its modern dimensions in the HE, while referring to the ways that is promoted within the European Area. The second section focuses on student mobility in the 21st century. First, there is a brief description of the history of mobility and then the relationship between mobility and the Bologna Process is outlined. In addition, student mobility programs are described as well as the evaluation of students’ experiences who participated in those programs, as shown in relevant research. Reference is also made to student mobility at the time of Covid-19 spread. Lastly, in the third section an attempt is made to link the processes of internationalization and mobility in Higher Education in Europe.